A Study of the Physical and Chemical Processes Involved in the Electroslag Remelting of a Low Alloy Steel - Whittaker, Donald (My University, 1967)
Low alloy steel electrodes have been electroslag remelted using alternating and direct current power sources. Changes in electrical contact between the furnace mould wall and mould base provided an improved understanding of the thermal ,and chemical processes characteristic of the remelting technique. 1m ion regeneration process has been postulated to account for current flow within the slag phase. Observed changes in furnace heating effects, electrode droplet sizes and in slag and metal compositions have be,en related to overtensions impressed on the slag/electrode and slag/ingot boundaries. The desulfurization reaction has been studied in detail.
Keywords: Electroslag Remelting; Low Alloy Steel; electrical contact; slag phase